Enhancing cognition by understanding knowledge flow characteristics during design collaboration - Ibrahim, Rahinah; Fay, Roger (Faculty of Design & Architecture, Universiti Putra Malaysia, 2006)
Organization researchers cannot fit the complex property development workflow processes with Galbraith’s information processing design theory, hence undermining attempts to ensure knowledge flow in complex multidisciplinary design collaborations. This survey paper summarizes recently completed studies at Stanford University on knowledge flows that affect organizational performance. The studies found that knowledge flows in functional knowledge areas differ from those in tacit knowledge areas. Future research will lead to the development of a knowledge management system for sustainable property development that considers the different dominant knowledge types during different design phases.